2004
DOI: 10.1185/030079904125004376
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home-acquired pneumonia: an emergency department treatment algorithm

Abstract: Nursing home-acquired pneumonia (NHAP) is a leading cause of morbidity, hospitalization, and mortality among older nursing home residents. Too often, these patients are erroneously grouped with cases of community-acquired and hospital-acquired pneumonia. Yet, they differ in terms of most common pathogens, significant underlying disease, impaired functional and cognitive status, and poor nutrition. The NHAP emergency department treatment algorithm presented here shows that an important decision for initial care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…1,2,[8][9][10]12,17,[20][21][22][23][24] The results from our study showed that CURB-65 and the pneumonia severity index were more accurate in predicting in-hospital mortality from NHAP compared with the other pneumonia severity scores. The findings are in agreement with previous studies 10,20,24 but in contrast to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[8][9][10]12,17,[20][21][22][23][24] The results from our study showed that CURB-65 and the pneumonia severity index were more accurate in predicting in-hospital mortality from NHAP compared with the other pneumonia severity scores. The findings are in agreement with previous studies 10,20,24 but in contrast to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 One common limitation to all these scoring models is that not one takes into consideration the functional status of nursing home residents. 3,12 Although NHAP was more severe than CAP, the proportion of subjects admitted to the ICU was similar, except in region II (28% vs 18%, P ϭ .09). We found that subjects with NHAP are older with a higher frequency of comorbidities.…”
Section: Presentation and Severitymentioning
confidence: 98%
“…However, it should be noted that outbreaks of Legionella infection have been reported in nursing homes. 3 Prospective clinical and environmental surveillance of nursing homes has revealed previously unsuspected Legionella infection because of colonization of the facilities' water supply by Legionella. 21 Viral infection in nursing homes is seasonal.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that the rate of CAP in the US is 18.2 cases per 1,000 person-years in persons aged 65 to 69 years, rises to 52.3 cases per 1,000 person-years in those aged 85 years and older, and in nursing home residents, the rates of CAP are estimated to be more than 300 cases per 1,000 person-years [5][6][7]. The annual incidence of invasive infections due to Streptococcus pneumoniae in adults older than 64 years in Chile, in a followup period of five years, has been reported to be 234/100,000 [8].…”
mentioning
confidence: 99%